Buerger’s and fried fingertips: a case of progressive buerger’s disease from secondhand smoke - Muna Aguon, Paul; Samareh-Jahani, Farmin; Kumar, Abhishek; Hamant, Laura; Franks Snedecor, Ruth (International Journal of Medicine, 2018)
We present a case of a 51-year-old Caucasian male with thromboangiitis obliterans who previously underwent multiple amputations and presented with poor wound healing post-amputation. Despite cessation of tobacco use, patient’s condition and wounds continued to worsen. After extensive and repeated history taking, it was discovered that his wife continued to be a heavy tobacco user and patient consistently had secondhand smoke exposure. This report describes an atypical presentation of progressive thromboangiitis obliterans as a result of secondhand smoke.